Interação entre as áreas funcionais do sistema visual e do sistema vestibular: estudo com RMF e EGV - Justina, Hellen Mathei Della (2014)
The static body equilibrium is controlled by three sensory systems: the vestibular system, responsible for informing the position and the movements of the head; the visual system, which informs the spatial objects position relative to the body; and the proprioceptive system, which controls posture and body movements. These three systems must always work in harmony, otherwise the individual will present balance problems. Thus, it is important to characterize the cortical regions, as well as their interactions, involved in this process. For this it is necessary to use functional neuroimaging techniques, the functional magnetic resonance imaging (fMRI) is one of the most used techniques in this field nowadays. However, a large fMRI experiments require the use of electronic devices for producing somatosensory stimulation in the human body, where the main difficulty is its hostile environment for electronic circuits. The galvanic vestibular stimulation is one of the most used methods to stimulate the vestibular system. This stimulation consist of applying a low current amplitude directly on vestibular afferents, which acts firing the primary vestibular neurons, affecting the otolithic afferents and the semicircular canals fibers. The objective of this work is to evaluate and analyze the brain areas involved with visual and galvanic vestibular stimulations and their interactions using fMRI. Therefore, as a first step of this research, a galvanic vestibular stimulator was validated in vivo. The electrical stimulator did not interfere in a significance way on magnetic resonance images quality and could be safely used in fMRI experiments. Tests were performed to select an electrode sufficiently comfortable for the volunteer during the galvanic vestibular stimulation and that do not cause artifacts in the images. After completed these steps, 24 subjects were selected to perform three tasks: a purely visual (a flashing checkerboard in the center of the screen), a purely vestibular (with application of galvanic vestibular stimulation) and a simultaneous, presenting the visual and vestibular stimuli together. The purely visual stimulation showed activation of the primary and associative visual cortices, while the purely vestibular stimulation led to activation of areas involved in multimodal function of the vestibular system, such as the parieto-insular vestibular cortex, the inferior parietal lobe, the superior temporal gyrus, the precentral gyrus and the cerebellum. The simultaneous stimulation of visual and vestibular systems resulted in activation of the middle and inferior frontal gyri. In addition to the reciprocal inhibitory visualvestibular interaction pattern had been more evident during the simultaneous condition, it was observed that frontal regions (dorsomedial prefrontal cortex and superior frontal gyrus) are involved with the executive function processing when there is conflicting information of visual and vestibular systems.